Lignin engineering in field-grown poplar trees affects the endosphere bacterial microbiome - Beckers, Bram (Proc Natl Acad Sci U S A, 2016)
Cinnamoyl-CoA reductase (CCR), an enzyme central to the lignin biosynthetic pathway, represents a promising biotechnological target to reduce lignin levels and to improve the commercial viability of lignocellulosic biomass. However, silencing of the CCR gene results in considerable flux changes of the general and monolignol-specific lignin pathways, ultimately leading to the accumulation of various extractable phenolic compounds in the xylem. Here, we evaluated host genotype-dependent effects of field-grown, CCR-down-regulated poplar trees (Populus tremula × Populus alba) on the bacterial rhizosphere microbiome and the endosphere microbiome, namely the microbiota present in roots, stems, and leaves. Plant-associated bacteria were isolated from all plant compartments by selective isolation and enrichment techniques with specific phenolic carbon sources (such as ferulic acid) that are up-regulated in CCR-deficient poplar trees. The bacterial microbiomes present in the endosphere were highly responsive to the CCR-deficient poplar genotype with remarkably different metabolic capacities and associated community structures compared with the WT trees. In contrast, the rhizosphere microbiome of CCR-deficient and WT poplar trees featured highly overlapping bacterial community structures and metabolic capacities. We demonstrate the host genotype modulation of the plant microbiome by minute genetic variations in the plant genome. Hence, these interactions need to be taken into consideration to understand the full consequences of plant metabolic pathway engineering and its relation with the environment and the intended genetic improvement.